Hubungan Pengetahuan Dan Sikap Ibu Dengan Pemberian Vitamin A Pada Balita Di Wilayah Kerja Puskesmas Pintu Angin Kota Sibolga Tahun 2023 - Yanthy Hutabatar; Magdalena Br Barus (Calory Journal Medical Laboratory Journal, 2023)
Vitamin A is essential for the maintenance of health and survival. In children under five due to VAC (Vitamin A deficiency) will increase morbidity and mortality, susceptible to infectious diseases such as diarrhea, pneumonia, pneumonia, and finally death. Vitamin A is useful for reducing mortality and morbidity, because vitamin A can increase the body's resistance to infectious diseases such as measles, diarrhea, and ARI Fullness of Puskesmas Pintu Angin This research uses a cross-sectional approach. As for the population in this study are mothers who have toddlers who visit the Kecepatan Health Center with a sample of 96 respondents.Based on the results of the study which were analyzed using chi-square, it was found that there is a relationship between knowledge and administration of vitamin A with a P-value of 0.009 and a PR of 1.909 (95% CI 1.186-3.074) and there is a relationship between attitudes and administration of vitamin A with a P-value. 0.001 and PR 2300 (95% CI 1.367-3,870). Expected for Mothers It is hoped that this research can increase mother's knowledge and become a source of information to the public about the benefits of giving vitamin A to toddlers.